Model rehabilitasi berpusat keluarga terintegrasi terapi medis pada spastisitas cerebral palsy (CP): A systematic literature review - Alami, Fidya Ifah; Najwa, Yusri Chizma (Holistik Jurnal Kesehatan, 2025)
Background: Cerebral palsy (CP) is a neurological disorder affecting motor function, posture, and overall quality of life in children. In children with spastic CP, medical therapies such as Bobath and hydrotherapy have shown positive outcomes in improving gross motor function, walking speed, reducing spasticity, and promoting muscle relaxation. Purpose: To analyze a family-centered rehabilitation model integrated with medical therapy in cerebral palsy (CP) spasticity. Method: A descriptive method with a qualitative approach through a Systematic Literature Review (SLR). Literature was analyzed based on relevance to family-centered rehabilitation, medical therapy interventions, and the ICF framework in pediatric spastic CP. Results: The study found that family involvement in rehabilitation significantly improves motor function, increases social participation, and strengthens adherence to home exercise routines. The integration of medical therapies with a supportive family-centered approach contributed to both physical improvement and psychosocial well-being, producing sustained positive effects on therapy outcomes and overall quality of life. Conclusion: There is a positive impact of combining medical therapy with a family-centered rehabilitation model in improving motor function, social participation, and adherence to home-based exercises in children with spastic cerebral palsy.   Keywords: Cerebral Palsy (CP) Spasticity; Family-Centered; Integrated Medical Therapy; Rehabilitation Model.   Pendahuluan: Cerebral palsy (CP) merupakan gangguan neurologis yang memengaruhi fungsi motorik, postur, dan kualitas hidup anak. Pada anak dengan CP spastik, terapi medis seperti Bobath dan hidroterapi terbukti memberikan dampak positif dalam meningkatkan fungsi motorik kasar, kecepatan berjalan, mengurangi spastisitas, serta memberikan relaksasi otot. Tujuan: Untuk menganalisis model rehabilitasi berpusat keluarga terintegrasi terapi medis pada spastisitas cerebral palsy (CP). Metode: Deskriptif dengan pendekatan kualitatif melalui systematic literature review (SLR). Literatur dianalisis berdasarkan relevansi terhadap model rehabilitasi berbasis keluarga, intervensi terapi medis, dan kerangka ICF pada CP spastik anak. Hasil: Keterlibatan keluarga dalam proses rehabilitasi berkontribusi signifikan terhadap peningkatan fungsi motorik anak, memperluas partisipasi sosial, serta memperkuat kepatuhan dalam menjalankan latihan di rumah. Integrasi antara terapi medis dan pendekatan berbasis keluarga juga memberikan dampak positif berkelanjutan pada efektivitas terapi dan kesejahteraan psikososial anak. Simpulan: Terdapat pengaruh positif dari integrasi terapi medis dengan model rehabilitasi berbasis keluarga dalam meningkatkan fungsi motorik, partisipasi sosial, dan kepatuhan latihan rumah pada anak dengan cerebral palsy spastik. Saran: Strategi rehabilitasi yang melibatkan dukungan keluarga secara aktif perlu diterapkan secara luas untuk meningkatkan efektivitas terapi dan kualitas hidup anak.   Kata Kunci: Berpusat Keluarga; Model Rehabilitasi; Spastisitas Cerebral Palsy (CP); Terintegrasi Terapi Medis.